The Effect of Backpack Load on Muscle Activities of the Trunk and Lower Extremities and Plantar Foot Pressure in Flatfoot - Son, Hohee (The Society of Physical Therapy Science, 2013)
[Purpose] The purpose of this study was to investigate the changes in muscle activation of the trunk and lower extremities and plantar foot pressure due to backpack loads of 0, 10, 15, and 20% of body weight during level walking in individuals with flatfoot. [Methods] Fourteen young flatfoot subjects and 12 normal foot subjects participated in this study. In each session, the subjects were assigned to carry a backpack load, and there were four level walking modes: (1) unloaded walking (0%), (2) 10% body weight (BW) load, (3) 15% BW load, and (4) 20% BW load. Trunk and lower extremity muscle activities were recorded by surface EMG, and contact area and plantar foot pressure were determined using a RS scan system. [Results] The erector spinae, vastus medialis, tibialis anterior and gastrocnemius muscle activities, but not the rectus femoris and rectus abdominis muscle activities of flatfoot subjects significantly and progressively increased as load increased in flatfoot subjects. Contact area and pressure of the lateral and medial heel zones were significantly increased too. [Conclusion] Based on this data, the weight of a backpack could influence muscle activation and plantar foot pressure in flatfoot.